2014
DOI: 10.1140/epjc/s10052-014-3129-3
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of differential cross sections for the production of a pair of isolated photons in pp collisions at $$\sqrt{s}=7\,\text {TeV} $$ s = 7 TeV

Abstract: A measurement of differential cross sections for the production of a pair of isolated photons in proton–proton collisions at is presented. The data sample corresponds to an integrated luminosity of 5.0 collected with the CMS detector. A data-driven isolation template method is used to extract the prompt diphoton yield. The measured cross section for two isolated photons, with transverse energy above 40 and 25 respectively, in the pseudorapidity range , and with an angular separation , is . Differential cross… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 43 publications
0
48
0
Order By: Relevance
“…Furthermore, it was recently found that the next-to-next-to-leading order (NNLO) correction that includes the effects of associated two-parton production is also large, as in the direct photon production [15,16]. Hence, this order of correction is necessary to be included in order to realistically reproduce the non-resonant diphoton production [17,18], although we still do not have any reasonable explanation on this large correction. Here, we note that the large NNLO correction is not predominantly caused by the emergence of new processes, e.g., gg → γγqq, but mainly originates from ordinary gluon-radiation corrections to one-parton production processes [15].…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, it was recently found that the next-to-next-to-leading order (NNLO) correction that includes the effects of associated two-parton production is also large, as in the direct photon production [15,16]. Hence, this order of correction is necessary to be included in order to realistically reproduce the non-resonant diphoton production [17,18], although we still do not have any reasonable explanation on this large correction. Here, we note that the large NNLO correction is not predominantly caused by the emergence of new processes, e.g., gg → γγqq, but mainly originates from ordinary gluon-radiation corrections to one-parton production processes [15].…”
Section: Introductionmentioning
confidence: 89%
“…We do not include resummation effects in the real-radiation because it is suppressed by a factor of β. The M (0) OC and M (1) OC (µ) denote the LO and NLO double-counted part of the amplitude as we discussed above. Note that the explicit dependence of M OC to respectively O(β 3 ) and O(β 2 ) using the expressions stated in Section 3.1.…”
Section: Matched Cross Sectionmentioning
confidence: 99%
“…The production of pairs of photons in hadronic collisions has attracted interest from both the experimental and the theory side for several decades. Most prominently, the diphoton final state served as one of the key discovery channels for the Higgs boson [1,2], which can decay into two photons. As a very clean experimental channel, it is also well suited for precision studies of the Standard Model (SM) and in particular the Higgs sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It played an essential role in the discovery of the Higgs boson [1,2] and in further refined measurements of fiducial cross sections and differential observables [3][4][5][6][7]. Due to its clean experimental signal, diphoton production in hadron collisions offers a testing ground for perturbative quantum chromodynamics and has been widely studied at the LHC [8][9][10][11][12]. This process is also an important search channel for new physics (see [13][14][15][16][17][18][19][20] for recent experimental searches).…”
Section: Introductionmentioning
confidence: 99%